2002
DOI: 10.1029/2000jb000062
|View full text |Cite
|
Sign up to set email alerts
|

Slow cooling of middle and lower oceanic crust inferred from multicomponent magnetizations of gabbroic rocks from the Mid‐Atlantic Ridge south of the Kane fracture zone (MARK) area

Abstract: [1] The remanent magnetization of gabbroic material of the Mid-Atlantic Ridge south of the Kane fracture zone (MARK) area provides constraints on both the thermal structure and tectonic history of the lower crust in this slow spreading environment. The remanence of these gabbroic samples is often complex, with the juxtaposition of intervals of apparently normal and reversed polarity rocks over small spatial scales (tens of centimeters to a few meters). Moreover, several samples when thermally demagnetized have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 72 publications
3
26
0
Order By: Relevance
“…This domain has a width of 6 km and probably represents the lower oceanic crust beneath the neo-volcanic zone, a zone that does not suffer significant rotational deformation (e.g., [40,41]). The width of the inferred lower crust neo-volcanic zone stands in agreement with the prediction of Gee and Meurer [34] for 6 km width of the region where magma is re-supplied into the lower crust at the Mid-Atlantic Ridge, south of Kane fracture zone.…”
Section: Figuresupporting
confidence: 76%
See 1 more Smart Citation
“…This domain has a width of 6 km and probably represents the lower oceanic crust beneath the neo-volcanic zone, a zone that does not suffer significant rotational deformation (e.g., [40,41]). The width of the inferred lower crust neo-volcanic zone stands in agreement with the prediction of Gee and Meurer [34] for 6 km width of the region where magma is re-supplied into the lower crust at the Mid-Atlantic Ridge, south of Kane fracture zone.…”
Section: Figuresupporting
confidence: 76%
“…These studies show that the characteristic remanent magnetization (ChRM) is primary and reside in magnetite. In addition, studies of the Oman ophiolite [31] and of the present-day oceanic crust (for example see [32][33][34]) have shown that the primary magnetic carrier is mostly low Ti-magnetite that acquired its magnetization during the initial intrusion time. According to their interpretation, the high temperature component of magnetization can be used to reconstruct the rigid body rotations of the lower crust.…”
Section: Previous Paleomagnetic Studiesmentioning
confidence: 99%
“…The early one layer models assume that the upper crust extrusive lavas make the strongest magnetic contribution, due to the high remanent magnetization of basalts, and have vertical polarity boundaries Irving et al, 1970;Talwani et al, 1971]. More recently, arguments have been made that the lower crust (gabbros) and upper mantle (serpentinized peridotites) rocks can have high natural remanent magnetizations (NRM) and represent significant magnetic sources in slow spreading ridge environments Gee and Meurer, 2002; Tivey and Tucholke, 1998]. Two-layer models frequently assume that polarity boundaries in the second layer, analogous to the gabbros in many cases, follow the curve of a conductively cooling isotherm that results in delayed acquisition of magnetization at depth [e.g.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Fresh peridotites in the upper mantle are weakly ferromagnetic (they are paramagnetic), but become strongly magnetic upon alteration to serpentinized peridotites. It has been assumed that serpentinized peridotites acquire their magnetization too slowly to contribute constructively to the to 75 % of the overall magnetic anomaly [Fox and Opdyke, 1973;Gee and Meurer, 2002; Tivey et al, 1998a; Tivey and Tucholke, 1998;Zhao et al, 2006]. Models of the magnetic source layer have consequently evolved into a two-layer approximation with an upper basalt layer and a lower intrusive layer [Dyment et al, 1997;.…”
mentioning
confidence: 99%
See 1 more Smart Citation